Conformational properties of quercetin: quantum chemistry investigation - Protsenko, I. O.; Hovorun, D.M. (Reports of the National Academy of Sciences of Ukraine, 2014)
The conformational analysis performed at the MP2/6–311++G(d,p)//DFT B3LYP/6-31G(d,p) theory level reveals as many as 12 conformations of a quercetin molecule with relative Gibbs energies from 0 to 5.4 kcal/mole. The spatial structure of the most energetically favorable conformation and its geometric characteristics have been found. It is found that a molecule of quercetin in the crystal state becomes much deformed to a nonplanar structure.